BET 1: Everything in graduation: arterial/end-tidal CO2 gradient and the diagnosis of pulmonary embolism. Issue 7 (22nd June 2021) - O'Rourke, John; MacDonald, Bethany
Abstract : A short cut review was carried out to establish the diagnostic characteristics of alveolar dead space fraction (AVDSf) in the diagnosis of pulmonary embolism (PE). This is calculated from the arterial and end-tidal CO2 . Three papers were selected to answer the clinical question. The author, study type, relevant outcomes, results and weaknesses are tabulated. It is concluded that there is good evidence to support the use of AVDSf within a clinical prediction model to exclude a PE in patients when there is a low pretest probability. However, the specificity is not sufficient to support it as a 'rule in' test.